2014
DOI: 10.1080/12538078.2013.870047
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary relict laurophyll vegetation in the Madonie mountains (Sicily)

Abstract: Abstract:: Laurel woodlands in the Madonie mountains (Sicily) are characterized by the presence of Laurus nobilis, Rhamnus lojaconoi and Vitis vinifera subsp. sylvestris. The results of a phytosociological study are presented, and a new endemic association, Rhamno lojaconoi-Lauretum nobilis, is described. Present Mediterranean laurel communities are the result of an adaptive response by Tertiary laurel forest to the peculiar microclimatic conditions that characterize the refugia where they persist. These refug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Indeed, in a dynamic or stable population structure, a high mortality rate at the juvenile stages of the propagules could limit the numbers of old individuals, thus, preventing the expansion of L. nobilis. Nevertheless, our conclusion about the potential expansion of L. nobilis in the study area is corroborated by the highly vital regeneration previously reported for several districts in Central Italy (Viciani and Moggi 1997;Foggi et al 2006), as well in populations in Northern and Southern Italy (Brullo and Guarino 1998;Bacchetta et al 2007;Gianguzzi et al 2010;Marino et al 2014) where we detected populations classified as dynamic or stable. A past vital regeneration combined with the current relatively high numbers of saplings found in these dynamic and stable populations therefore suggest a well-established recruitment process of L. nobilis, both in time and space.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, in a dynamic or stable population structure, a high mortality rate at the juvenile stages of the propagules could limit the numbers of old individuals, thus, preventing the expansion of L. nobilis. Nevertheless, our conclusion about the potential expansion of L. nobilis in the study area is corroborated by the highly vital regeneration previously reported for several districts in Central Italy (Viciani and Moggi 1997;Foggi et al 2006), as well in populations in Northern and Southern Italy (Brullo and Guarino 1998;Bacchetta et al 2007;Gianguzzi et al 2010;Marino et al 2014) where we detected populations classified as dynamic or stable. A past vital regeneration combined with the current relatively high numbers of saplings found in these dynamic and stable populations therefore suggest a well-established recruitment process of L. nobilis, both in time and space.…”
Section: Discussionsupporting
confidence: 91%
“…But some recent phylogeographical and/or paleoecological studies provide sometimes counterintuitive results. For some sclerophyllous species (the laurel tree Laurus nobilis: Rodríguez-Sánchez et al 2009;Marino et al 2014; the myrtle, Myrtus communis: Migliore et al 2012) that are not domesticated but only used by humans, the classical hypothesis of an eastern Mediterranean origin followed by subsequent westward expansion and diversification across the western Mediterranean and Macaronesia is verified. These cases suggest here a limited influence of historical human-mediated translocations despite the ancient use of these species.…”
Section: The Complex Native Status Of Domesticated or Useful Mediterrmentioning
confidence: 99%
“…caprificus, has been described by Bacchetta et al [15]. On the contrary, Gianguzzi et al [16] and Marino et al [17] have found in Sicily residual L. nobilis communities with a limited presence of C. australis, where the latter was not considered characteristic of the newly described association.…”
Section: Introductionmentioning
confidence: 78%